Clinical Focus on Prosodic, Discursive and Pragmatic Treatment for Right Hemisphere Damaged Adults: What's Right?. (12th January 2011) - Ferré, Perrine; Ska, Bernadette; Lajoie, Camille; Bleau, Amélie; Joanette, Yves
Abstract : Researchers and clinicians acknowledge today that the contribution of both cerebral hemispheres is necessary to a full and adequate verbal communication. Indeed, it is estimated that at least 50% of right brain damaged individuals display impairments of prosodic, discourse, pragmatics and/or lexical semantics dimensions of communication. Since the 1990's, researchers have focused on the description and the assessment of these impairments and it is only recently that authors have shown interest in planning specific intervention approaches. However, therapists in rehabilitation settings still have very few available tools. This review of recent literature demonstrates that, even though theoretical knowledge needs further methodological investigation, intervention guidelines can be identified to target right hemisphere damage communication impairments in clinical practice. These principles can be incorporated by speech and language pathologists, in a structured intervention framework, aiming at fully addressing prosodic, discursive and pragmatic components of communication.